Double hyperautofluorescent ring on fundus autofluorescence in ABCA4. (2nd January 2018) - Abalem, Maria Fernanda; Qian, Cynthia X.; Branham, Kari; Schlegel, Dana; Fahim, Abigail T.; Khan, Naheed W.; Heckenlively, John R.; Jayasundera, K. Thiran
ABSTRACT: We report an unusual phenotype in a child with a clinical diagnosis of recessive Stargardt disease (STGD1) and two pathogenic variants in the ABCA4 gene. Typically, the diagnosis of early-onset STGD1 is challenging because children may present with a variety of fundus changes and a variable rate of progression. At the time of his initial visit, the 6-year-old boy presented with 20/200 OD (right eye) and 20/150 OS (left eye), symmetrical mild foveal atrophy without flecks on fundus exam, and foveal hypoautofluorescence surrounded by a homogeneous hyperautofluorescent background on wide-field fundus autofluorescence. Over 4 years of follow-up, the retinal atrophy continued to progress, resulting in two well-defined and concentric hyperautofluorescent rings: one ring located at the posterior pole and the other located around the peripapillary region. Visual acuity also deteriorated to counting fingers at 4ft OD and 20/500 OS. To the best of our knowledge, this phenotype has not been previously described with the ABCA4 gene.